Integrated management of childhood illness with the focus on caregivers: an integrative literature review La atención integrada de las enfermedades prevalentes en la infancia y el enfoque en los cuidadores: revisión integradora de la literatura Atenção integrada às doenças prevalentes na infância e o enfoque nos cuidadores: revisão integrativa da literatura - Vania Daniele Paranhos; Juliana Coelho Pina; Débora Falleiros de Mello (Universidade de São Paulo, 2011)
The Integrated Management of Childhood Illness (IMCI) strategy addresses the diseases most prevalent in infancy, the reception of the child and family, and the comprehension the problem and effective procedures. The aim was to identify, between 1998 and 2008, publications relating to the IMCI strategy focusing on the caregiver. This study is an Integrative literature review in the Pubmed, Lilacs and Scielo databases. The caregivers knew one or more warning signs for acute respiratory infection, but not for diarrhea. Pneumonia was perceived as a serious childhood disease. Communication skills among health professionals trained in the IMCI strategy were different to those in untrained professionals. The follow-up of the health of the child is higher according to the education level of the caregiver, and according to the medications supplied in the consultation and in the follow-up. Regarding the health of the child it is relevant to focus on the IMCI strategy, favoring experiences that include the family in the care. La estrategia Atención Integrada a las Enfermedades Prevalentes en la Infancia (AIEPI) aborda las enfermedades de mayor prevalencia en la infancia, el acogimiento del niño y de la familia, la comprensión del problema y los procedimientos eficaces. El objetivo fue identificar, entre 1998 y 2008, publicaciones relacionadas a la estrategia AIEPI con enfoque en el cuidador. Revisión integradora con evidencias en la literatura, en las bases de datos Pubmed, Lilacs y Scielo. Los cuidadores conocen una o más señales de alarma para infección respiratoria aguda, pero no para diarrea. La neumonía es percibida como una grave enfermedad infantil. Las habilidades comunicativas entre los profesionales de la salud capacitados en la estrategia AIEPI y los no capacitados son diferentes. El seguimiento de la salud del niño es mayor de acuerdo con la escolaridad del cuidador, los medicamentos ofrecidos en la consulta y el retorno. En la salud del niño es relevante enfocar la estrategia AIEPI, favoreciendo vivencias que incluyan a la familia en el cuidado. A estratégia atenção integrada às doenças prevalentes na infância (AIDPI) aborda as doenças de maior prevalência na infância, o acolhimento da criança e família, a compreensão do problema e procedimentos eficazes. O objetivo foi identificar, entre 1998 e 2008, publicações relativas à estratégia AIDPI com enfoque no cuidador. Foi realizada revisão integrativa com evidências da literatura, nas bases de dados PubMed, LILACS e SciELO. Os cuidadores sabem um ou mais sinais de alarme para infecção respiratória aguda, mas não para diarreia. A pneumonia é percebida como grave doença infantil. As habilidades comunicativas entre os profissionais de saúde capacitados na estratégia AIDPI e os não capacitados são diferentes. O seguimento da saúde da criança é maior de acordo com a escolaridade do cuidador, os medicamentos fornecidos na consulta e o retorno. Na saúde da criança, é relevante enfocar a estratégia AIDPI, favorecendo vivências que incluam a família no cuidado.